New characterization of dihydroergotamine receptor pharmacology in the context of migraine: utilization of a β-arrestin recruitment assay - McConnachie, Lisa; Goadsby, Peter J.; Vann, Robert E.; Ray, Sutapa; Shrewsbury, Stephen B.; Aurora, Sheena K. (Frontiers in Neurology, 2023)
Introduction Dihydroergotamine mesylate (DHE) is an established effective acute therapy for migraine and is often characterized by its broad receptor pharmacology. Knowledge of DHE pharmacology largely comes from studies employing older methodologies. Objective To assess DHE receptor activity using high-throughput methods to screen for functional ß-arrestin activity at G protein–coupled receptors (GPCRs). Methods Functional receptor activities of DHE and sumatriptan succinate (both 10 μM) were screened against 168 GPCRs using the gpcrMAX assay. Agonist and antagonist effects were considered significant if receptor activity was >30% or inhibited by >50%, respectively. Radiolabeled ligand binding assays were performed for DHE (0.01–300 nM for 5-HT3 and 4E; 0.3–10,000 nM for 5-HT1B, α-adrenergic2B [i.e., α2B-adrenoceptor], D2, and D5) to assess specific binding to select receptors. Results DHE (10 μM) exhibited agonist activity at α-adrenergic2B, CXC chemokine receptor 7 (CXCR7), dopamine (D)2/5, and 5-hydroxytryptamine (5-HT)1A/1B/2A/2C/5A receptors and antagonist activity at α-adrenergic1B/2A/2C (i.e., α1B/2A/2C-adrenoceptors), calcitonin receptor–receptor activity modifying protein 2 (CTR-RAMP2) or amylin 2 (AMY2), D1/3/4/5, and 5-HT1F receptors. Sumatriptan succinate (10 μM) exhibited agonist activity at the 5-HT1B/1E/1F/5A receptors. DHE demonstrated a half-maximal inhibitory concentration (IC50) of 149 nM at the 5-HT1F receptor and a half-maximal effective concentration (EC50) of 6 μM at the CXCR7 receptor. DHE did not bind to the 5-HT3 receptor at concentrations up to 300 nM and bound poorly to 5-HT4E and D5 receptors (IC50 of 230 and 370 nM, respectively). DHE bound strongly to the D2, 5-HT1B, and α-adrenergic2B receptors (IC50 of 0.47, 0.58, and 2.8 nM, respectively). Conclusion By using a high-throughput β-arrestin recruitment assay, this study confirmed the broad receptor profile of DHE and provided an update on DHE receptor pharmacology as it relates to migraine.